2012
DOI: 10.1016/s1995-7645(12)60013-3
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial potential of sponge endosymbiont marine Enterobacter sp at Kavaratti Island, Lakshadweep archipelago

Abstract: The present study concluded that phylogenetic analysis of endosymbiotic bacteria Enterobacter sp from sponge D. granulosa of Lakshadweep islands showed significant antibacterial activity against clinical bacterial pathogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…In recent years, several studies have been focused on the isolation of cytotoxic molecules from sponges having active secondary metabolites against broad spectrum of clinical and marine pathogens [9]. More in details, these authors demonstrated that bacteria isolated from sponges have been found to exhibit antibacterial activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, several studies have been focused on the isolation of cytotoxic molecules from sponges having active secondary metabolites against broad spectrum of clinical and marine pathogens [9]. More in details, these authors demonstrated that bacteria isolated from sponges have been found to exhibit antibacterial activity.…”
Section: Introductionmentioning
confidence: 99%
“…More in details, these authors demonstrated that bacteria isolated from sponges have been found to exhibit antibacterial activity. The secondary metabolites of host sponge D. granulosa have confirmed significant antimicrobial activity and inhibited the growth of clinical pathogens [9]. …”
Section: Introductionmentioning
confidence: 99%
“…Earlier reports revealed that the organic extract from S. carnosa exhibited weak activity against the tested bacteria and fungi except Fusarium sp. [18][19][20][21] .…”
Section: Discussionmentioning
confidence: 99%
“…This was kept in shaker at 100 rpm for 24 hours, and centrifuged at 12 000 rpm for 20 minutes. Followed, the supernatant was filtered through Whatman No.…”
Section: Preparation Of Sponge Extractionmentioning
confidence: 99%
“…There are in all 36 islands, which are invariably surrounded by huge and shallow lagoons at the western side [8,9]. The morphologic location of the Indian ocean is unique from other oceans, as it is surrounded completely by land in the northern side and it doesn’t extend in low temperature zones of the northern hemisphere [10].…”
Section: Introductionmentioning
confidence: 99%